Coma scales: a historical review - Ana Luisa Bordini; Thiago F. Luiz; Maurício Fernandes; Walter O. Arruda; Hélio A.G. Teive (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To describe the most important coma scales developed in the last fifty years. METHOD: A review of the literature between 1969 and 2009 in the Medline and Scielo databases was carried out using the following keywords: coma scales, coma, disorders of consciousness, coma score and levels of coma. RESULTS: Five main scales were found in chronological order: the Jouvet coma scale, the Moscow coma scale, the Glasgow coma scale (GCS), the Bozza-Marrubini scale and the FOUR score (Full Outline of UnResponsiveness), as well as other scales that have had less impact and are rarely used outside their country of origin. DISCUSSION: Of the five main scales, the GCS is by far the most widely used. It is easy to apply and very suitable for cases of traumatic brain injury (TBI). However, it has shortcomings, such as the fact that the speech component in intubated patients cannot be tested. While the Jouvet scale is quite sensitive, particularly for levels of consciousness closer to normal levels, it is difficult to use. The Moscow scale has good predictive value but is little used by the medical community. The FOUR score is easy to apply and provides more neurological details than the Glasgow scale.